Severe mitochondrial encephalomyopathy caused by de novo variants in OPA1 gene - Di Nottia, Michela; Rizza, Teresa; Baruffini, Enrico; Nesti, Claudia; Torraco, Alessandra; Diodato, Daria; Martinelli, Diego; Dal Canto, Flavio; Gilea, Alexandru Ionut; Zoccola, Martina; Siri, Barbara; Dionisi-Vici, Carlo; et al. (Frontiers in Genetics, 2024)
Mitochondria adjust their shape in response to the different energetic and metabolic requirements of the cell, through extremely dynamic fusion and fission events. Several highly conserved dynaminlike GTPases are involved in these processes and, among those, the OPA1 protein is a key player in the fusion of inner mitochondrial membranes. Hundreds of monoallelic or biallelic pathogenic gene variants have been described in OPA1, all associated with a plethora of clinical phenotypes without a straightforward genotype-phenotype correlation. Here we report two patients harboring novel de novo variants in OPA1. DNA of two patients was analyzed using NGS technology and the pathogenicity has been evaluated through biochemical and morphological studies in patient's derived fibroblasts and in yeast model. The two patients here reported manifest with neurological signs resembling Leigh syndrome, thus further expanding the clinical spectrum associated with variants in OPA1. In cultured skin fibroblasts we observed a reduced amount of mitochondrial DNA (mtDNA) and altered mitochondrial network characterized by more fragmented mitochondria. Modeling in yeast allowed to define the deleterious mechanism and the pathogenicity of the identified gene mutations.We have described two novel-single OPA1 mutations in two patients characterized by early-onset neurological signs, never documented, thus expanding the clinical spectrum of this complex syndrome. Moreover, both yeast model and patients derived fibroblasts showed similar mitochondrial defects, including decreased mtDNA maintenance, correlating with patients' clinical phenotypes.